Osteomyelitis and lung abscess due to Aspergillus fumigatus in a chronic granulomatous disease patient - Setareh Mamishi; Kamiar Zomorodian; Farshid Saadat; Seyedeh Zohreh Jalali; Mohsen Geramishoar (Mazandaran University of Medical Sciences, 2016)
Background and Purpose: Chronic granulomatous disease (CGD) is an inherited disorder of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex. This disorder results in recurrent life-threatening bacterial and fungal infections. Aspergillus species are the most common fungal infections in these patients. Case Report: Herein, we present a case of fungal infection in a girl with CGD. We confirmed aspergillosis through the positive microscopic and macroscopic examinations, as well as radiology results. Invasive aspergillosis in this patient with pneumonia, lung abscess, and osteomyelitis of the ribs was not initially treated with amphotericin B (Am B) and recombinant interferon-gamma. Conclusion: Among infectious diseases, fungal infections, in particular aspergillosis, remain a serious problem in CGD patients. Considering poor clinical response and deficient immune system, rapid diagnosis of fungal infection and optimizing the treatment of these patients are recommended.